2017
DOI: 10.1186/s41038-017-0101-0
|View full text |Cite
|
Sign up to set email alerts
|

The significance of changes in platelet concentration during the early phase after severe burn injury in a Chinese mass casualty

Abstract: BackgroundChanges in platelet concentration are common in severe burn patients. Platelets play a key role in the course of disease. This study aims to explore the significance of platelet concentration during the course of the disease in victims of a mass burn casualty.MethodsA total of 180 patients were involved in the “8.2” Kunshan explosion accident in China. The examined data included age, gender, total burn area (% TBSA), third-degree burn area (% TBSA), and platelet concentration within the first 5 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This is because when damage occurs, platelets are trapped as microthrombi. Then the platelets are mobilized for coagulation as part of the thrombotic process, resulting in a very high consumption of platelets 6 . The decrease in platelet levels in T2 is also in line with the results of previous studies where the administration of melatonin did not have an effect in the form of an increase in platelets at 24 hours after burn, but on the contrary, platelet levels continued to decrease for 24 hours after burns 13 .…”
Section: Discussionmentioning
confidence: 99%
“…This is because when damage occurs, platelets are trapped as microthrombi. Then the platelets are mobilized for coagulation as part of the thrombotic process, resulting in a very high consumption of platelets 6 . The decrease in platelet levels in T2 is also in line with the results of previous studies where the administration of melatonin did not have an effect in the form of an increase in platelets at 24 hours after burn, but on the contrary, platelet levels continued to decrease for 24 hours after burns 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study of patients with severe burn injuries, Yang and colleagues, 2014, found concentrations of serum creatinine and plasma and urine neutrophil gelatinase-associated lipocalin to be associated with early acute kidney injury (AKI) and early mortality. In a study of an aluminum dust explosion in China, blood platelet concentrations collected from severely burned victims in the five days following the injury were significantly lower in patients who developed AKI and higher in patients who experienced successful resuscitation (Shou et al, 2017). A retrospective analysis of 24 patients admitted to a burn unit with either sepsis or septic shock following a water park explosion in Taiwan found significantly higher serum procalcitonin levels among patients with septic shock, while measurements of the other potential biomarkers were not significantly different between the two groups (Wu et al, 2017).…”
Section: Laboratory Testingmentioning
confidence: 99%
“…Thrombocy-topenia, as an indicator of an increased process of inflammatory response and intravascular coagulation, may also be a very early marker of the risk of septic shock, which usually develops fully only in the second or third week after thermal trauma. In this work, immediate administration of anti-infective treatment in all burn patients with thrombocytopenia was postulated [24].…”
Section: Thrombocytopeniamentioning
confidence: 99%